Subjective recollection independent from multifeatural context retrieval following damage to the posterior parietal cortex. (June 2017) - Ciaramelli, Elisa; Faggi, Giorgia; Scarpazza, Cristina; Mattioli, Flavia; Spaniol, Julia; Ghetti, Simona; Moscovitch, Morris
Abstract: This study investigated whether damage to the posterior parietal cortex (PPC) impairs the capacity to retrieve multiple aspects of the encoding context in which items were studied, or whether it impairs the subjective awareness of recollection. Patients with lesions to the PPC (PPC patients) and healthy controls memorized words along with the position in which the words were presented on the screen and the ink color in which they were printed. We studied PPC patients' recognition and source memory performance, as well as subjective recollection as indexed by Remember/Know judgments. PPC patients had preserved recognition memory, and gave a similar number of R responses as did controls. Moreover, PPC patients' source memory performance, including memory for multiple contextual features, was similar to the controls'. However, whereas healthy controls were more likely to select R responses with correct multifeatural source judgments compared to K responses, PPC patients were not. These findings indicate that the PPC plays a role in the subjective experience and metamnemonic evaluation of memory contents.